Aldehyde-alcohol Dehydrogenase Forms A High-order Spirosome Architecture Critical For Its Activity - Gijeong Kim; Liyana Azmi; Seongmin Jang; Taeyang Jung; Hans Hebert; Andrew J. Roe; Olwyn Byron; Ji-Joon Song (Nature Publishing Group, 2024)
Indexed by ERA